Land Sale and Purchase Through a Power of Attorney Deed - Dahris Siregar; Muhammad Dhobit Azhary Lubis (Green Publisher, 2025)
This research examines the legal implications of granting a notarial power of attorney for land sale and purchase transactions. A normative juridical method is used in this sort of study. This study was conducted qualitatively and look at primary and secondary legal materials thoroughly. The aim of this study is to determine the legal foundation of sale and purchase contractual agreements, the authority to sell and/or release rights and whether the notary or PPAT violates laws and principles. A notary official grants a notary power of attorney in writing. The findings revealed that, from the standpoint of Conventional law, A selling and purchase contract with A legal type is a power of attorney. of authentic deed that fits the agreement's legal requirements, according to The Civil Code, Article 1320. However, a binding document of sale and purchase is not a requirement for a land transaction under agrarian law. This is due to the fact that transactions relating to land can only be considered valid and if the deed is signed by an official authorized to make a land deed.